2004
DOI: 10.1177/153537020422900704
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Plays an Important Role in the Pathogenesis of Drug-Induced Retinopathy

Abstract: Several pharmaceutical agents have been associated with rare but serious retinopathies, some resulting in blindness. Little is known of the mechanism(s) that produce these injuries. Mechanisms proposed thus far have not been embraced by the medical and scientific communities. However, preclinical and clinical data indicate that oxidative stress may contribute substantially to iatrogenic retinal disease. Retinal oxidative stress may be precipitated by the interaction of putative retinal toxins with the ocular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 84 publications
(98 reference statements)
3
43
0
Order By: Relevance
“…It is known that LPO is an important mechanism in acute and chronic CPZ intoxication (Khatua and Bhattacharyya 2001). Previous studies have indicated the implication of oxidative stress in hepatic tissue damage induced by CPZ treatment, manifested by MDA elevation in liver tissue (Parola et al 1996), which can be explained as a consequence of generation of CPZ cation radicals and/or metabolic activation of CPZ to quinoneimine derivatives (Toler 2004). Retention of hydrophobic bile acids and toxic substances and infiltration of inflammatory cells may participate in the generation of ROS with consequent production of oxidative damage (Casini et al 308 Fig .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that LPO is an important mechanism in acute and chronic CPZ intoxication (Khatua and Bhattacharyya 2001). Previous studies have indicated the implication of oxidative stress in hepatic tissue damage induced by CPZ treatment, manifested by MDA elevation in liver tissue (Parola et al 1996), which can be explained as a consequence of generation of CPZ cation radicals and/or metabolic activation of CPZ to quinoneimine derivatives (Toler 2004). Retention of hydrophobic bile acids and toxic substances and infiltration of inflammatory cells may participate in the generation of ROS with consequent production of oxidative damage (Casini et al 308 Fig .…”
Section: Discussionmentioning
confidence: 99%
“…4AQs promoted oxidation of cysteine residues in the peripherin/rds protein leading to disorganization of photoreceptor outer segments and cell death [ 29 ] 24. Chloroquine had a direct depressant effect on smooth muscle of the gut, arteries, trachea, and ciliary body, which might explain the mild ileus and temporary presbyopia that patients often experience after starting the drug [ 100 ] 25.…”
Section: Negative Studies On Mechanism Of Action Of 4-aminoquinolinesmentioning
confidence: 99%
“…The inhibition of lysosomal enzymatic function is hypothesized to be the cause of benefi cial effects and retinopathy of the 4AQs [ 29 ]. Once inside lysosomes, 4AQs inhibit the lysosomal activity of cathepsin B and enzymes involved in degradation of mucopolysaccharides and proteins [ 33 , 71 , 118 , 165 , 166 ].…”
Section: Positive Studies On Mechanism Of Action Of 4-aminoquinolinesmentioning
confidence: 99%
“…In both chloroquine retinopathy and ARMD, decreased lysosomal function and oxidative stress are present [3,4] . For patients with chloroquine retinopathy antioxidative therapy might be benefi cial as found for ARMD patients in the AREDS study [4] .…”
Section: Discussionmentioning
confidence: 99%
“…(2) Chloroquine accumulates in the retinal pigment epithelium (RPE) and the choroid, binding to melanin [2] . (3) Chloroquine treatment induces oxidative stress: it was found that glutathione (GSH) is reduced and lipid peroxidation increased during chloroquine treatment [3] .…”
Section: Introductionmentioning
confidence: 99%